Synergistic Effects of Trichoderma harzianum and Fluorescent Pseudomonads on Sheath Blight Management and Growth Promotion in Rice: Sheath Blight Management using Trichoderma harzianum and Fluorescent Pseudomonads - Singh, Ankit Kumar; Singh , Ram (Journal of Cereal Research, 2025)
Rice, being a staple food for a significant portion of the world's population, faces persistent threats from diseases like sheath blight, which can severely impact yield and quality. The present study reports the potential of employing beneficial microbes, specifically Trichoderma harzianum and Pseudomonas fluorescens isolates, for both sheath blight management and growth promotion in rice (Oryza sativa L.). Both T. harzianum and P. fluorescens isolates were evaluated as seed bio-priming and seedling root dipping treatments. The most significant increase in plant height occurred in treatments where seeds were bio-primed and seedling roots were treated with T. harzianum isolate IRRI-1 followed by T. harzianum isolate SV-3 and Pseudomonas fluorescens isolate PF-2.  Employing both seed bio-priming and seedling root dipping methods with T. harzianum (IRRI-1), followed by P. fluorescens (PF-4) and T. harzianum (SV-3) yielded the most substantial increases in fresh and dry root weights. Similarly, plants treated with bio-priming using T. harzianum (IRRI-1), followed by T. harzianum (SV-26), and P. fluorescens (PF2) exhibited the highest fresh and dry weights of rice shoots. IRRI-1 significantly increased chlorophyll content to 71.86 and 94.22 over control, respectively, by seed biopriming and seedling root dipping. Notable sheath blight reduction was observed in seed bio-priming using T. harzianum (IRRI-1), T.  harzianum (SV-3), and P. fluorescens (PF4). However, the efficacy of these bioagents varied slightly when applied through seedling root dipping, where T. harzianum (IRRI-1) followed by P. fluorescens (PF4) and T. harzianum (SV-19) demonstrated the highest effectiveness in reducing sheath blight levels. In summary, seed bio-priming appeared to be comparatively more effective for promoting rice growth, whereas seedling root dipping exhibited greater efficacy in managing sheath blight. In summary, seed bio-priming emerged as comparatively more effective for promoting rice growth, while seedling root dipping demonstrated greater efficacy in managing sheath blight.